PENERAPAN METODE TOPSIS PADA SISTEM PENDUKUNG KEPUTUSAN UNTUK PEMILIHAN TANAMAN HIAS BONSAI - Dolok Saribu, Enjeli Vista Bela; Marbun, Murni (STMIK Kaputama, 2020)
Many customers who need ornamental plants provide good prospects for the future of ornamental plant business specifically for ornamental plant farmers. Ornamental plants are not limited to ornamental plants that live in pots, but also include cut flowers, cacti, bonsai, hydroponic plants and flower screens. This study aims to create a Decision Support System (SPK) for selecting ornamental bonsai plants. Criteria for selecting bonsai ornamental plants have a beautiful basic shape, long plant decorations, stems and branches are easily made, the surface of the skin is attractive and curvy, small leafy and quite leafy, plant plants are durable and strong plants to be made. The system was built with Visual Basic Programming language and applied the TOPSIS method to determine bonsai ornamental plants. Implementation of decision support systems choose from 5 (five) alternative choices of plants that are worthy of being ornamental bonsai plants are Banyan, Chinese Asoka and Jasmine.